ANALISIS SISTEM PEMASARAN SAPI POTONG - Ria Ashari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2018)
In the context of national development, West Nusa Tenggara Province has been prioritized as one of the areas / regions of beef cattle and once as a beef cattle purification area that is expected to be a provider / stock of national beef cattle in a sustainable manner while maintaining its sustainability, especially Bali cattle (Livestock Service NTB Province, 2011). Cows are the most efficient commodity in converting animal feed into animal protein. Cattle breeders in Nusa Tenggara Province are generally family businesses in small-scale rural areas, while large-scale businesses are still very limited and generally are a newly grown dairy business. The composition of cattle farmers is estimated to consist of 80% of small farmers with less than four cows, 17% of farmers with 4-7-tailed cattle ownership and 3% of farmers with ownership of 7 cows. The average selling price of beef cattle at the producer level is Rp 16,435.05 / kg live weight, Rp 16,539.34 / kg live weight and Rp 17,066.51 / kg live weight. The selling price of beef cattle at the level of recipient traders is Rp 16,952.73 / kg live weight, Rp 17,288.57 / kg live weight and Rp 18,208.29 / kg live weight. The average selling price of beef cattle at the cutter / retailer level is Rp. 17,529.57 / kg live weight, Rp. 18,344.06 / kg live weight and Rp. 20,125.75 / kg live weight. The average selling price of beef cattle at the retailer level is Rp. 17,557.55 / kg of live weight. The selling price of beef cattle at the agent level is Rp. 17,804.85 / kg of live weight. The selling price of beef cattle at the trader level is Rp. 20,125.75 / kg of live weight. Based on these price differences, the total marketing margins on average in each marketing channel are Rp 1,135.41 / kg live weight, Rp 2,154.74 / kg live weight and Rp 2,828.94 / kg live weight, respectively.